Nanotechnological approaches for management of soil-borne plant pathogens - Dutta, Pranab; Kumari, Arti; Mahanta, Madhusmita; Upamanya, Gunadhya Kr; Heisnam, Punabati; Borua, Sarodee; Kaman, Pranjal K.; Mishra, A. K.; Mallik, Meenakshi; Muthukrishnan, Gomathy; Sabarinathan, Kuttalingam G.; Puzari, Krishti Rekha; et al. (Frontiers in Plant Science, 2023)
Soil borne pathogens are significant contributor of plant yield loss globally. The constraints in early diagnosis, wide host range, longer persistence in soil makes its management cumbersome and difficult. Therefore, it is crucial to devise innovative and effective management strategy to combat the losses caused by soil borne diseases. The use of chemical pesticides is the mainstay of current plant disease management practices that potentially cause ecological imbalance. Nanotechnology presents a suitable alternative to overcome the challenges associated with diagnosis and management of soil-borne plant pathogens. This review probes the use of nanotechnology for soil-borne disease management by various means including nanoparticle alone as protectant, as carrier of actives such as pesticides, fertilizers, antimicrobial agents and RNAi molecules or by stimulation of plant growth and development. Nanotechnology can also be used for precise and accurate detection of soil-borne pathogens for devising efficient management strategy. The unique physico-chemical properties of nanoparticles allow greater penetration and interaction with biological membrane and thereby increasing its efficacy and releasability. However, the nanoscience specifically agricultural nanotechnology is still in its toddler stage and to realize its full potential, extensive field trials, utilization of pest crop host system and toxicological studies is essential to tackle the fundamental queries associated with development of commercial nano-formulations.